PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MOTIVASI KEWIRAUSAHAAN TERHADAP KEBERHASILAN BERWIRAUSAHA ANAK MUDA DI SURABAYA - Astuti, Aryani Puji; Novaria, Rachmawati; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2020)
This study aims to determine the effect of Entrepreneurship Education and Entrepreneurship Motivation Variables on Entrepreneurial Success simultaneously, partially and as the dominant variabel. The method used in this research is quantitative research with data collection techniques using purposive sampling. Data collection techniques used are by distributing questionnaires. Young people who have received entrepreneurship courses while studiying, while the number is not known with certainty. The number of sampels obtained as many as 100 people. This research produces (1.) simultaneously the variables of entrepreneurship education (X1) and entrepreneurial motivation (X2) simultaneously have a positive and significant on Entrepreneurial interest (Y) (2.) Partially shows that entrepreneurship education has a positive but not significant effect on entrepreneurial success (3.) entrepreneurial motivation variable also has a positive and significant effect on entrepreneurial success.Keyword : entrepreneurship education, motivation and entrepreneurial success